The Influence of Poverty and Unemployment on the Number of Crimes in Pekanbaru City - Aswanto; Emkhad Arif (PT Syamilah Literasi Islami, 2024)
The aim of this research is to analyze the influence of the percentage of poor people and the number of unemployed on the number of crimes in Pekanbaru City, Riau Province. Meanwhile, the data used is secondary data sourced from BPS Pekanbaru City from 2017 to 2022. The results of this research show that the percentage of poor people has a positive and significant effect on the number of crimes reported, while the number of unemployed has a negative and significant effect on the number of crimes reported. reported in Pekanbaru City. The data analysis model used is an econometric model with multiple linear analysis equations and uses the E-Views 13 application as research data processing. Based on the results of this research, it is hoped that the government and all groups will create security and order so that crime does not occur and implement programs that can create prosperity in the economy of the people of Pekanbaru City.